ОБ’ЄКТ ТА ПРЕДМЕТ АДМІНІСТРАТИВНО-ПРАВОВОГО ЗАБЕЗПЕЧЕННЯ ДІЯЛЬНОСТІ ЮРИДИЧНИХ ВІДДІЛІВ - Кривко, Ольга Олегівна (SUPREMANCE OF LAW, 2019)
The article, based on the analysis of scientific views of scientists, identifies and characterizes the object and subject of administrative and legal support of legal departments. It was found that the object of administrative and legal support of legal departments are public relations, which arise in the process offormation, implementation and termination of legal status of legal departments. It is stated that the concept of “subject” is narrower than “the object of administrative and legal support of legal departments” It is substantiated that the subject of the relevant provision consists of the following groups of legal relations: 1) legal relations related to the formation, reorganization and liquidation of the relevant departments; 2) legal relations related to the direct organization of the work of legal departments, in particular: logistical, financial, staffing, etc.; 3) legal relations related to ensuring effective interaction between employees within the department, as well as between legal departments and other structural units. It is generalized that the object and subject of administrative and legal support of legal departments are interrelated categories. They relate to each other as a whole and a fraction. In more detail, the subject indicates the specific boundaries and framework within which the administrative and legal support affects the object. Thus, it can be argued that in the framework of the presented scientific issues the subject outlines in more detail the legal relations that make up the content of legal departments and directly fall under the regulatory influence of administrative law in general and the mechanism of administrative support in particular.
Keywords: object; subject; administrative and legal support; legal departments; legislation; administrative law